The Influence of The Cooperative Learning Model with Type of Talking Stick on Students Learning Outcomes in Economic Subjects Class X Social Sciences Sman 1 Rantau Pulung - Muh. Fiqri Nurrahmatullah; Reza Reza; Riyo Riyadi (Faculty of Teacher Training and Education, Mulawarman University, 2021)
This study aims to determine: (1) The use of cooperative learning model type talking stick in economics subjects class X social science SMAN 1 Rantau Pulung; (2) The achievement of economic learning outcomes from the cooperative learning model of the type talking stick in students of class X social science SMAN 1 Rantau Pulung; (3) The Use of cooperative learning model type talking stick effect of the on economic learning outcomes in students of class X social science SMAN 1 Rantau Pulung. This research is a quantitative research type of quasi-experimental research or quasi-experimental, research with research subjects namely students of class X Social Sciences SMA Negeri 1 Rantau Pulung with class X social science 2 as many as 23 people as experimental class and class X social science 3 as many as 26 people as control class. Data collection is done by using the test technique. Based on the results of the descriptive analysis, the average for the experimental class increased by 12.54% while the average value for the control class experienced a slight decrease of 0.44%. Through the results of hypothesis testing, the sig value is obtained. (2-tailed) t-test for Equality of Means is 0.005 so that the significance value is <0.05, which means that H0 is rejected or Ha is accepted. So, it can be concluded that there is a significant effect of the talking stick type cooperative learning model on the economic learning outcomes of class X social studies students at SMA Negeri 1 Rantau Pulung.